KOMUNIKASI BISNIS PENGUSAHA DODOL NANGKA UD WARNA SARI DALAM MENINGKATKAN HASIL PENJUALAN DI DESA SURANADI KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - Eka Permadi, I Gusti Agung Didit (Widya Sandhi, 2019)
Communication is a medium of importance various thing to face life. Communication business holding on role very importance sales some thing product. Communication business could in the form of verbal and non verbal. Communication business is done by businessman dodol jack fruit (UD Warna Sari) in the village Suranadi Narmada District West Lombok Regency is very influence sustainability business jackfruit dodol that is to sales to consumers. Aim of research this are :1) to method Sari, 2) to knowi strategy of UD Warna Sari business in improve total sales jackfruit dodol. Method of the research is qualitative . With informant main is owner of UD Warna Sari and informant others that is UD Warna Sari employees. Result sresearch :1) Commocation UD Warna Sari business done Sari is communication verbally and non verbal well to consumer, inside marketing and communication with employee. 2) Business Strategy UD. Warna Sari inside improve total sales is with way promotion in a manner directly to consumers who come to his industy, followed UMKM exhibitions, and improving quality export to market outside of the country.